The performance of leaching experiments to assess the potential mobilization of trace elements during CO2 injection. (September 2020) - Wilkinson, Mark; Carruthers, Kit; Thomas, Alexander L.; Haszeldine, R. Stuart
Abstract: To control reservoir pressure during CO2 injection for Carbon Capture and Storage, it may be necessary to produce native porewaters to the surface. These porewaters could contain potentially toxic metals mobilised from the reservoir rock by the injected CO2, which would then be discharged into the ocean if offshore, or treated if onshore. To evaluate the risk, both chip and grain samples from a UK North Sea sandstone that is a candidate for CO2 storage were exposed to CO2 -saturated water in 30 day leaching experiments, and the metal load of the porewaters was analysed. Only Pb and Zn were convincingly mobilised (median 30 vs 2 μg/L for Pb; 130 vs 25 μg/L for Zn), and these elements have been previously reported to be more easily mobilised in experiments than during in-situ CO2 injection. Hence, in this case, the risk of releasing toxic metals into the environment is assessed as small, and comparable to existing hydrocarbon operations. Results are significantly variable within a single sandstone reservoir, suggesting that experiments with multiple samples are required to make a realistic assessment of leaching potential. An assessment of other potential chemical data for assessing trace metal leaching suggested that only the comparatively lengthy leaching experiments generated useful data. Highlights: The mobility of 8 potentially toxic trace metals is low in the presence of high concentrations of CO2 . Concentrations are similar to those of natural brine from the reservoir. Arsenic concentrations notably decreased in the presence of CO2 . Only Pb and Zn were mobilised by CO2  but have been reported as more mobile in experiments than in-situ CO2  injection. Leaching experiments appear to be the only practical way to assess trace metal loading.